Speciation of Cr(III) and Cr(VI) in aqueous solution and their removal by oyster mushroom biomass - Asif, M N M; Islam, Rashedul; Goni, MA; Ganguli, Sumon; Chakraborty, Ashok Kumar; Kabir, Mahbub; Sabur, Md Abdus (Journal of Bangladesh Academy of Sciences, 2023)
This study investigates the effectiveness of oyster mushroom (Pleurotus platypus) for the removal of Cr(III) and Cr(VI) from aqueous solutions by conducting a series of batch adsorption experiments. Results from the adsorption pH envelope experiments show that while the adsorption of Cr(III) increases with increasing pH, the adsorption of Cr(VI) decreases as the pH rises. These two distinct pH envelope patterns for Cr(III) and Cr(VI) suggest that the adsorption processes are primarily driven by the electrostatic force of attractions followed by the ligand exchange process. Findings from the adsorption isotherm experiments demonstrate that chromium binding to the adsorbent surface is better described by the Freundlich model than the Langmuir model, underscoring the presence of multiple surface binding sites. The study highlights the significance of identifying dominant chromium species before they are subjected to adsorptive removal from contaminated waters. J. Bangladesh Acad. Sci. 47(2); 267-275: December 2023